Modified graphite-based silicon-carbon negative electrode material as well as preparation method and application thereof
Through the preparation method of modified graphite-based silicon carbon negative electrode material, the problem of volume expansion and powderization of silicon negative electrode during charging and discharging is solved, and the effects of stable structure, excellent conductivity and high capacity are achieved.
Patent Information
- Application Number
- CN202411853906.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-03-21
AI Technical Summary
The existing silicon negative electrode volume expansion and powderization during charging and discharging, resulting in capacity attenuation, reduced cycle life and damage to the electrode structure, limiting its large-scale commercial application.
Using the preparation method of modified graphite-based silicon-carbon negative electrode material, a silicon carbon negative electrode material is mixed with a dispersing solvent, spray granulation and curing, followed by carbonization, activation and silicon deposition in the protective gas, and finally carbon coating is carried out to form a silicon-carbon negative electrode material with stable structure and excellent conductivity.
The structural stability, low expansion rate, good rate performance and excellent conductivity of the modified graphite-based silicon carbon anode material are achieved, effectively improving the capacity, and alleviating the problems of excessive expansion rate and poor rate performance of the silicon anode.
Smart Images

Figure CN119674005A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion battery materials, and in particular to a modified graphite-based silicon-carbon negative electrode material and a preparation method and application thereof. Background Art
[0002] Lithium-ion batteries are widely used in various energy storage devices due to their high energy density and long cycle life. Existing graphite anode lithium battery storage devices can no longer meet people's requirements for high-capacity storage devices. Silicon anode, as a resource with abundant resources, safety and non-toxicity, and a theoretical specific capacity of 4200mAh / g, is considered to be one of the most promising materials to replace graphite anode.
[0003] However, the existing silicon negative electrode shows high volume expansion and material pulverization during the charge and discharge process, leading to capacity attenuation, reduced cycle life and electrode structure damage, which limits its large-scale commercial application. Graphite has a low specific surface area, but its surface is difficult to etch, which means that graphite cannot carry more silicon through silane deposition.
[0004] Chinese patent CN 117577819 A uses porous carbon materials deposited with nano-silicon and nano-silicon-lithium alloy as the core to prepare silicon-carbon negative electrode materials, but this method uses solid-phase lithium hydride as the deposited lithium source, and the uniformity of silicon-lithium deposition is difficult to control. The particle size of the silicon-lithium alloy skeleton in the prepared silicon-carbon negative electrode material is difficult to be consistent, which affects the electrochemical performance of the material. Chinese patent CN 116885133 A uses multiple carbon layers to coat the silicon-carbon negative electrode to alleviate the volume expansion of the silicon-carbon negative electrode, but multiple carbon layer coatings prolong the process preparation time, and too many carbon layers will reduce the rate charge and discharge performance of the silicon-carbon negative electrode. Summary of the invention
[0005] The purpose of the present invention is to provide a modified graphite-based silicon-carbon negative electrode material and a preparation method and application thereof. The prepared modified graphite-based silicon-carbon negative electrode material has a stable structure, low expansion rate, good rate performance, excellent conductivity, and both high gram capacity and high initial efficiency.
[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0007] The present invention provides a method for preparing a modified graphite-based silicon-carbon negative electrode material, comprising the following steps:
[0008] The graphite, the carbon source, the conductive agent and the dispersion solvent are mixed, and the obtained dispersion is spray granulated and solidified in sequence to obtain a solid phase mixture;
[0009] In a first protective gas, carbonizing the solid phase mixture to obtain a modified graphite-based carbon precursor;
[0010] In a second protective gas, activating the modified graphite-based carbon precursor to obtain a modified graphite-based hierarchical porous carbon skeleton;
[0011] In the third protective gas, silane gas is introduced to deposit silicon on the modified graphite-based hierarchical porous carbon skeleton, and then carbon source gas is introduced to perform carbon coating to obtain a modified graphite-based silicon-carbon negative electrode material.
[0012] Preferably, the particle size of the graphite is 0.5 to 20 μm; the carbon source includes one or more of asphalt, resin, cellulose, glucose and coconut shell carbon, and the mass ratio of the graphite to the carbon source is 1:1 to 5.
[0013] Preferably, the conductive agent comprises one or two of multi-walled carbon nanotubes, single-walled carbon nanotubes, graphene, vapor-grown carbon fibers and carbon fibers, the mass of the conductive agent is 0.01 to 15% of the total mass of the graphite and the carbon source, and the mixing time of the graphite, the carbon source, the conductive agent and the dispersion solvent is 0.5 to 10 hours;
[0014] The dispersion solvent is water or an organic solvent, and the solid content of the dispersion is 5 to 50 wt %;
[0015] The curing temperature is 100-180° C. and the curing time is 1-20 hours.
[0016] Preferably, the carbonization temperature is 650-1100° C., the time is 1-5 hours, and the heating rate to the carbonization temperature is 1-5° C. / min.
[0017] Preferably, the first protective gas, the second protective gas and the third protective gas independently include one or more of N2, Ar and He.
[0018] Preferably, the activation method includes physical activation or alkali activation;
[0019] The activation gas used for the physical activation includes CO2 and / or H2O; the flow rate of the activation gas is 0.5 to 5 L / min;
[0020] The solid activator used for the alkali activation includes one or more of NaOH, KOH and K2CO3; the mass ratio of the modified graphite-based carbon precursor to the solid activator is 1:1-10.
[0021] Preferably, the activation temperature is 650-1100° C., the time is 1-5 h; and the heating rate to the activation temperature is 1-5° C. / min.
[0022] Preferably, the silane gas includes one or two of monosilane, disilane and chlorosilane; the flow ratio of the silane gas to the third protective gas is 1:1-10; the flow rate of the silane gas is 0.2-8 L / min; the temperature of the silicon deposition is 400-1000°C, the time is 2-8h, and the heating rate is 2-10°C / min;
[0023] The carbon source gas includes one or more of methane, ethane, acetylene and propyne; the flow ratio of the carbon source gas to the third protective gas is 1:1-10; the flow rate of the carbon source gas is 0.2-8L / min; the temperature of the carbon coating is 500-1000°C, the time is 2-8h, and the heating rate is 2-10°C / min.
[0024] The present invention provides a modified graphite-based silicon-carbon negative electrode material prepared by the preparation method described in the above technical solution, wherein the Si content is 10-90wt% and the carbon content is 10-90wt% based on the total content of 100wt%.
[0025] The present invention provides the use of the modified graphite-based silicon-carbon negative electrode material described in the above technical solution in a lithium-ion battery.
[0026] The present invention provides a method for preparing a modified graphite-based silicon-carbon negative electrode material. The present invention uses graphite as a core, combines a modified carbon material on its outer surface, and obtains a silicon-carbon negative electrode material through silane deposition and carbon coating. The modified graphite-based silicon-carbon negative electrode material prepared by the present invention uses small-particle graphite as a core, can provide more lithium ion migration channels and silicon deposition sites, thereby improving the rate performance. The presence of the graphite core increases the structural stability of the silicon-carbon negative electrode and improves the cycle stability of the silicon-carbon negative electrode; at the same time, a modified hierarchical porous carbon skeleton layer is coated on the outer surface of the graphite core, providing more pore defects for silicon deposition, providing more conduction / transmission paths for electrons / ions, and improving the ability of the silicon-carbon negative electrode to desorb / absorb lithium ions; finally, a carbon layer is coated on the outer surface to avoid direct contact between active silicon and electrolyte, reduce the consumption of active lithium, achieve structural stability during the charge and discharge process of the silicon-carbon negative electrode, and improve the rate charge and discharge performance and cycle stability of the silicon-carbon negative electrode during the charge and discharge process; at the same time, the addition of a conductive agent provides an excellent conductive network and better conductivity for the silicon-carbon negative electrode. Therefore, the modified graphite-based silicon-carbon negative electrode material prepared by the present invention has a stable structure, low expansion rate, good rate performance, and excellent conductivity, which can effectively improve the gram capacity to a certain extent and alleviate the problems of excessive expansion rate and poor rate performance of the silicon negative electrode. The silicon-carbon negative electrode material prepared by this method combines the advantages of graphite negative electrode and silicon negative electrode, and has both high gram capacity and high initial efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 The present invention is a flow chart of the preparation method of the modified graphite-based silicon-carbon negative electrode material;
[0028] Figure 2 It is a schematic structural diagram of the modified graphite-based silicon-carbon negative electrode material of the present invention; wherein, 1-graphite core, 2-modified carbon layer, 3-silicon deposition point, 4-coated carbon layer. DETAILED DESCRIPTION
[0029] In the present invention, unless otherwise specified, the required raw materials or reagents are commercially available products well known to those skilled in the art.
[0030] like Figure 1 As shown, the present invention provides a method for preparing a modified graphite-based silicon-carbon negative electrode material, comprising the following steps:
[0031] The graphite, the carbon source, the conductive agent and the dispersion solvent are mixed, and the obtained dispersion is spray granulated and solidified in sequence to obtain a solid phase mixture;
[0032] In a first protective gas, carbonizing the solid phase mixture to obtain a modified graphite-based carbon precursor;
[0033] In a second protective gas, activating the modified graphite-based carbon precursor to obtain a modified graphite-based hierarchical porous carbon skeleton;
[0034] In the third protective gas, silane gas is introduced to deposit silicon on the modified graphite-based hierarchical porous carbon skeleton, and then carbon source gas is introduced to perform carbon coating to obtain a modified graphite-based silicon-carbon negative electrode material.
[0035] The invention mixes graphite, a carbon source, a conductive agent and a dispersing solvent, and sequentially sprays and granulates the obtained dispersion to obtain a solid phase mixture.
[0036] In the present invention, the particle size of the graphite is preferably 0.5 to 20 μm; the carbon source preferably includes one or more of asphalt, resin, cellulose, glucose and coconut shell carbon. When the carbon source is more than two of the above, the present invention has no special limitation on the ratio of different types of carbon sources, and any ratio is acceptable.
[0037] In the present invention, the resin is preferably a phenolic resin.
[0038] In the present invention, the mass ratio of the graphite to the carbon source is preferably 1:1 to 5, more preferably 1:1.
[0039] In the present invention, the conductive agent preferably includes one or two of multi-walled carbon nanotubes, single-walled carbon nanotubes, graphene, vapor grown carbon fiber (VGCF) and carbon fiber. When the conductive agent is the above two types, the present invention has no special limitation on the ratio of different types of conductive agents, and any ratio is acceptable.
[0040] In the present invention, the mass of the conductive agent is preferably 0.01 to 15% of the total mass of the graphite and the carbon source, and more preferably 0.075%.
[0041] In the present invention, the mixing time of the graphite, carbon source, conductive agent and dispersion solvent is preferably 0.5 to 10 hours, more preferably 2 to 6 hours.
[0042] In the present invention, the dispersion solvent is preferably water or an organic solvent, and the organic solvent preferably includes NMP (N-methylpyrrolidone), DMC (dimethyl carbonate) or EC (ethylene carbonate); the solid content of the dispersion is preferably 5-50wt%, more preferably 20-30wt%.
[0043] The present invention has no special limitation on the conditions of the spray drying, and a spray dryer known in the art can be used. The present invention adheres the carbon source and the conductive agent to the surface of the graphite particles by spray granulation.
[0044] In the present invention, the curing temperature is preferably 100-180°C, more preferably 120-150°C, the curing time is preferably 1-20 hours, more preferably 5-10 hours; the curing is preferably carried out in a protective atmosphere, and the gas used in the protective atmosphere is preferably one or more of N2, Ar and He. During the curing process, the raw materials are physically combined.
[0045] In the present invention, the first protective gas, the second protective gas and the third protective gas preferably independently include one or more of N2, Ar and He; when the protective gas is two or more of the above, the present invention has no special limitation on the ratio of different types of protective gases, and any ratio is acceptable.
[0046] In the present invention, the carbonization temperature is preferably 650-1100°C, more preferably 750-800°C, the time is preferably 1-5h, more preferably 2-3h, and the heating rate to the carbonization temperature is preferably 1-5°C / min, more preferably 2-4°C / min. During the carbonization pyrolysis process, the carbon layer coated on the outside of the graphite combines with the conductive agent and forms a partial pore structure as the gas is released.
[0047] In the present invention, the activation method preferably includes physical activation or alkali activation; the activation gas used in the physical activation preferably includes CO2 and / or H2O; the flow rate of the activation gas is preferably 0.5-5L / min, more preferably 1-3L / min; when the activation gas is two of the above, the present invention has no special limitation on the ratio of different types of activation gases, and any ratio is acceptable.
[0048] In the present invention, the solid activator used for alkali activation preferably includes one or more of NaOH, KOH and K2CO3; when the solid activator is two or more of the above, the present invention has no special limitation on the ratio of different types of solid activators, and any ratio is acceptable; the mass ratio of the modified graphite-based carbon precursor to the solid activator is preferably 1:1 to 10, more preferably 1:3 to 6. When a solid activator is used for activation, the present invention preferably mixes the modified graphite-based carbon precursor and the solid activator in a desired mass ratio for activation.
[0049] In the present invention, the activation temperature is preferably 650-1100°C, more preferably 800-850°C, the time is preferably 1-5h, more preferably 2-3h; the heating rate to the activation temperature is preferably 1-5°C / min, more preferably 2-4°C / min. The present invention generates more pores on the carbon layer coated on the graphite surface through activation, thereby forming a larger specific surface area.
[0050] After completing the activation, the present invention preferably washes and dries the obtained product in sequence to obtain a modified graphite-based hierarchical porous carbon skeleton. The washing time is preferably 2 to 36 hours, the drying temperature is preferably 80 to 150°C, more preferably 100 to 120°C, and the drying time is preferably 1 to 20 hours, more preferably 3 to 12 hours.
[0051] In the present invention, the silane gas preferably includes one or two of monosilane, disilane and chlorosilane; the flow ratio of the silane gas to the third protective gas is preferably 1:1-10, more preferably 1:1-5; the flow rate of the silane gas is preferably 0.2-8L / min, more preferably 2-5L / min; the temperature of the silicon deposition is preferably 400-1000°C, more preferably 550-800°C, the time is preferably 2-8h, more preferably 4-5h, and the heating rate is preferably 2-10°C / min, more preferably 4-5°C / min. When the silane gas is two or more of the above, the present invention has no special limitation on the ratio of different types of silane gas, and any ratio is acceptable.
[0052] In the present invention, the carbon source gas preferably includes one or more of methane, ethane, acetylene and propyne; the flow ratio of the carbon source gas to the third protective gas is preferably 1:1-10, more preferably 1:1-5; the flow rate of the carbon source gas is preferably 0.2-8L / min, more preferably 2-5L / min; the temperature of the carbon coating is preferably 500-1000°C, more preferably 600-850°C, the time is preferably 2-8h, more preferably 4-5h, and the heating rate is preferably 2-10°C / min, more preferably 4-5°C / min. When the carbon source gas is two or more of the above, the present invention has no special limitation on the ratio of different types of carbon source gases, and any ratio is acceptable.
[0053] The present invention adopts a vapor deposition method to carry out silicon deposition and carbon coating, and can deposit nano silicon more uniformly in the carbon layer.
[0054] The present invention provides a modified graphite-based silicon-carbon negative electrode material prepared by the preparation method described in the above technical scheme, wherein, based on the total content of 100wt%, the Si content is 10-90wt%, and the carbon content is 10-90wt%; the Si content is more preferably 46-54wt%, further preferably 48-52wt%, and further preferably 50wt%, and the carbon content is more preferably 48-54wt%, and further preferably 50-52wt%.
[0055] like Figure 2 As shown, the modified graphite-based silicon-carbon negative electrode material prepared by the present invention has graphite as the core (graphite core 1), the surface of the graphite layer is coated with a modified carbon layer 2 containing silicon deposition points 3, and the outer layer is a coated carbon layer 4.
[0056] The present invention provides the application of the modified graphite-based silicon-carbon negative electrode material described in the above technical solution in a lithium-ion battery. The present invention has no special limitation on the application method, and the application can be carried out according to methods well known in the art.
[0057] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0058] In the following cases, the particle size of the graphite used is 0.5-20 μm; the water-based single-walled carbon nanotubes (solid content 0.4%, TUBALL TM BATT H2O 0.4%); coconut shell carbon and resin porous carbon both come from Shengquan (both passed through a 500-mesh sieve before use); multi-walled carbon nanotubes (solid content 0.4%, Shenzhen Deyi Nanotechnology Co., Ltd.);
[0059] Example 1
[0060] S1. Graphite, coconut shell carbon and single-walled carbon nanotubes (CNT) in a mass ratio of 1:1:0.0015 are added to water, the solid content of the obtained dispersion is controlled at 20wt%, and the mixture is dispersed by stirring for 2h; then granulated by a spray dryer, and then dried and cured at 150°C for 10h under the condition of passing N2 to obtain a solid phase mixture;
[0061] S2, heating the obtained solid phase mixture to 800° C. at a heating rate of 4° C. / min under N2 protection conditions for carbonization for 3 h to obtain a modified graphite-based carbon precursor;
[0062] S3, placing the obtained modified graphite-based carbon precursor in a rotary kiln, heating it to 850°C at a heating rate of 4°C / min under the condition of N2, and then introducing 1L / min of CO2 for activation for 3h; after the activation, washing it with water for 2h, and drying it at 150°C for 3h, to obtain a modified graphite-based hierarchical porous carbon skeleton;
[0063] S4. Place the modified graphite-based hierarchical porous carbon skeleton obtained in S3 into a rotary kiln, heat it to 550°C at a heating rate of 4°C / min, introduce monosilane (monosilane gas flow rate: N2 flow rate = 1:1) under the condition of passing N2, the monosilane gas flow rate is 5 L / min, and silicon deposition is carried out for 4 hours; then heat it to 850°C at a heating rate of 4°C / min, introduce acetylene gas (acetylene gas flow rate: N2 flow rate = 1:1) under the condition of passing N2, the acetylene gas flow rate is 5 L / min, and carbon coating is carried out for 4 hours to obtain a modified graphite-based silicon-carbon negative electrode material, wherein the Si content is 52wt% and the carbon content is 48wt%.
[0064] Example 2
[0065] The only difference from Example 1 is that the carbon source in step S1 is replaced by phenolic resin instead of coconut shell carbon; the carbonization temperature in step S2 is 750° C. and the holding time is 3 h; and the other conditions remain unchanged.
[0066] In the prepared modified graphite-based silicon-carbon negative electrode material, the Si content is 50wt% and the carbon content is 50wt%.
[0067] Example 3
[0068] The only difference from Example 1 is that the conductive agent in step S1 is replaced by multi-walled carbon nanotubes instead of single-walled carbon nanotubes CNT; the drying and curing stage is carried out at 120° C. for 5 h under the condition of N2; and the other conditions remain unchanged.
[0069] In the prepared modified graphite-based silicon-carbon negative electrode material, the Si content is 48wt% and the carbon content is 52wt%.
[0070] Example 4
[0071] The only difference from Example 1 is that the conductive agent in step S1 is replaced by vapor-grown carbon fiber VGCF instead of single-walled carbon nanotube CNT; the activation temperature in step S3 is controlled at 800° C. and the activation time is controlled at 3 h; and the other conditions remain unchanged.
[0072] In the prepared modified graphite-based silicon-carbon negative electrode material, the Si content is 46wt% and the carbon content is 54wt%.
[0073] Example 5
[0074] The only difference from Example 1 is that in step S4, the silane gas is replaced by disilane from monosilane, and the deposition time is 5 hours; the other conditions remain unchanged.
[0075] The prepared modified graphite-based silicon-carbon negative electrode material has a Si content of 54 wt% and a carbon content of 46 wt%.
[0076] Comparative Example 1
[0077] The only difference from Example 1 is that no conductive agent is added in step S1; the other conditions remain unchanged, and the Si content in the prepared silicon-carbon negative electrode material is 52wt% and the carbon content is 48wt%.
[0078] Comparative Example 2
[0079] The only difference from Example 2 is that no conductive agent is added in step S1; the other conditions remain unchanged, and the Si content in the prepared silicon-carbon negative electrode material is 50wt% and the carbon content is 50wt%.
[0080] Comparative Example 3
[0081] The only difference from Example 1 is that in step S1, graphite is replaced by resin porous carbon; the other conditions remain unchanged, and the prepared silicon-carbon negative electrode material has a Si content of 52wt% and a carbon content of 48wt%.
[0082] Characterization and performance testing
[0083] The modified graphite-based silicon-carbon negative electrode materials obtained in Examples 1 to 5 and the silicon-carbon negative electrode materials obtained in Comparative Examples 1 to 2 were subjected to performance tests under the following test conditions:
[0084] The prepared negative electrode material, carbon black, conductive agent and binder were mixed in a mass ratio of 94:1:1:4, wherein carbon black (passed through a 500-mesh sieve, Tianjin Ruiyat Chemical Co., Ltd.), the conductive agent was aqueous single-walled carbon nanotubes (solid content 0.4%, TUBALL TMBATT H2O 0.4%), binder LA132 (solid content 0.2%, Zhengzhou Alpha Chemical Co., Ltd.); assembled into button cells (positive electrode is lithium sheet, negative electrode is electrode sheet), tested on the blue power test system, the results are shown in Table 1.
[0085] Table 1 Performance test results of materials in Examples 1 to 5 and Comparative Examples 1 to 3
[0086]
[0087]
[0088] It can be seen from Table 1 that the modified graphite-based silicon-carbon negative electrode material prepared in the embodiment of the present invention exhibits more excellent electrochemical performance (first charge specific capacity, first efficiency and capacity retention rate) than the comparative example.
[0089] It can be seen from the above embodiments that the present invention provides a method for preparing a modified graphite-based silicon-carbon negative electrode material. The prepared modified graphite-based silicon-carbon negative electrode material has small-particle graphite as the core, and is coated with a modified graded porous carbon layer on its surface, which provides more pore defects for silicon deposition and improves the ability of the silicon-carbon negative electrode to desorb / adsorb lithium ions; finally, a carbon layer is coated on the surface of the silicon-carbon negative electrode to avoid direct contact between active silicon and electrolyte, reduce the consumption of active lithium, achieve structural stability during the charge and discharge process of the silicon-carbon negative electrode, and improve the rate charge and discharge performance of the silicon-carbon negative electrode and the cycle stability during the charge and discharge process; at the same time, due to the addition of the conductive agent, an excellent conductive network is provided for the silicon-carbon negative electrode.
[0090] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a modified graphite-based silicon-carbon negative electrode material, characterized in that: The following steps are involved: The graphite, the carbon source, the conductive agent and the dispersion solvent are mixed, and the obtained dispersion is spray granulated and solidified in sequence to obtain a solid phase mixture; In a first protective gas, carbonizing the solid phase mixture to obtain a modified graphite-based carbon precursor; In a second protective gas, activating the modified graphite-based carbon precursor to obtain a modified graphite-based hierarchical porous carbon skeleton; In the third protective gas, silane gas is introduced to deposit silicon on the modified graphite-based hierarchical porous carbon skeleton, and then carbon source gas is introduced to perform carbon coating to obtain a modified graphite-based silicon-carbon negative electrode material.
2. The preparation method according to claim 1, characterized in that: The particle size of the graphite is 0.5-20 μm; the carbon source includes one or more of asphalt, resin, cellulose, glucose and coconut shell carbon, and the mass ratio of the graphite to the carbon source is 1:1-5.
3. The preparation method according to claim 1 or 2, characterized in that: The conductive agent includes one or two of multi-walled carbon nanotubes, single-walled carbon nanotubes, graphene, vapor-grown carbon fibers and carbon fibers, the mass of the conductive agent is 0.01-15% of the total mass of the graphite and the carbon source, and the mixing time of the graphite, the carbon source, the conductive agent and the dispersion solvent is 0.5-10 hours; The dispersion solvent is water or an organic solvent, and the solid content of the dispersion is 5 to 50 wt %; The curing temperature is 100-180° C. and the curing time is 1-20 hours.
4. The preparation method according to claim 3, characterized in that: The carbonization temperature is 650-1100° C., the time is 1-5 hours, and the heating rate to the carbonization temperature is 1-5° C. / min.
5. The preparation method according to claim 1, characterized in that: The first protective gas, the second protective gas and the third protective gas independently include one or more of N2, Ar and He.
6. The preparation method according to claim 5, characterized in that: The activation method includes physical activation or alkali activation; The activation gas used for the physical activation includes CO2 and / or H2O; the flow rate of the activation gas is 0.5 to 5 L / min; The solid activator used for the alkali activation includes one or more of NaOH, KOH and K2CO3; the mass ratio of the modified graphite-based carbon precursor to the solid activator is 1:1-10.
7. The preparation method according to claim 6, characterized in that: The activation temperature is 650-1100° C., and the time is 1-5 hours; the heating rate to the activation temperature is 1-5° C. / min.
8. The preparation method according to claim 7, characterized in that: The silane gas includes one or two of monosilane, disilane and chlorosilane; the flow ratio of the silane gas to the third protective gas is 1:1-10; the flow rate of the silane gas is 0.2-8 L / min; the temperature of the silicon deposition is 400-1000°C, the time is 2-8h, and the heating rate is 2-10°C / min; The carbon source gas includes one or more of methane, ethane, acetylene and propyne; the flow ratio of the carbon source gas to the third protective gas is 1:1-10; the flow rate of the carbon source gas is 0.2-8L / min; the temperature of the carbon coating is 500-1000°C, the time is 2-8h, and the heating rate is 2-10°C / min.
9. The modified graphite-based silicon-carbon negative electrode material prepared by the preparation method according to any one of claims 1 to 8, characterized in that: Based on the total content of 100wt%, the Si content is 10-90wt%, and the carbon content is 10-90wt%.
10. Use of the modified graphite-based silicon-carbon negative electrode material according to claim 9 in lithium-ion batteries.
Citation Information
Patent Citations
Silicon-carbon composite material as well as preparation method and application thereof
CN116885133A
Cited By
Silicon-carbon negative electrode material based on spherical starch porous carbon and preparation method of silicon-carbon negative electrode material
CN120039880A
Preparation method of silicon-carbon-graphite composite negative electrode material and application thereof
CN122739263A